Assessing the degree of personal exposure to PM2.5 in growing cities of Rwanda based on time-activity patterns and microenvironments - Abdou Safari Kagabo; Bonfils Safari; Jimmy Gasore; Bethwel Kipkoech Mutai (City and Environment Interactions)
Long-term exposure to fine particulate matter (PM2.5) is strongly linked with a wide range of diverse health effects making it a substantial global threat and a critical concern for public health. While studies have been conducted on personal exposure (PE) to PM2.5 in specific environments, contributions of different microenvironments and activities to overall daily PE remain unclear. This study evaluates the degree of PE to PM2.5 in five growing cities of Rwanda based on individual’s time-activity patterns and visited microenvironments. A total of 150 participants were recruited to collect real-time personal and ambient PM2.5 measurements during their routine activities in different outdoor and indoor microenvironments for five consecutive days in dry season. Each participant was an employee in one of the six most prevalent urban economic activities found in their city of residence: workshops, flour mill plants, near road activities, garages, markets, kitchens and motorcycle taxi services. The participant’s day was categorized into three most distinct microenvironments grouped under home, work, and other microenvironments (other MEs). PE to PM2.5 assessed for all participants showed significant variability among types of activities and categories of microenvironments (p < 0.05). The work microenvironment experienced the highest daily mean PM2.5 exposures ranging from 12.67 μg/m3 to 192.64 μg/m3, followed by other MEs ranging from 13.25 μg/m3 to 113.58 μg/m3, while the lowest exposures observed at home microenvironment with concentrations ranging from 11.69 μg/m3 to 72.54 μg/m3 among 7 monitored activities in 5 cities. Exposure contributions and personal-ambient differences were dominated by the work microenvironment, with a daily contribution of flour milling activities reaching up to 51.55 %; and some participants were exposed to maximum PM2.5 concentrations up to 22 times higher than ambient levels while in the kitchen activities. This study highlights the significant effects of daily personal activities and visited microenvironments on personal PM2.5 exposure, and the importance of considering a personal lifestyle in understanding the true personal exposure.